2021
DOI: 10.1007/s40122-021-00269-6
|View full text |Cite
|
Sign up to set email alerts
|

Pain Relief and Safety Outcomes with Cervical 10 kHz Spinal Cord Stimulation: Systematic Literature Review and Meta-analysis

Abstract: Background: Chronic pain in head, neck, shoulders and upper limbs is debilitating, and patients usually rely on pain medications or surgery to manage their symptoms. However, given the current opioid epidemic, non-pharmacological interventions that reduce pain, such as spinal cord stimulation (SCS), are needed. The purpose of this study was to review the evidence on paresthesia-free 10 kHz SCS therapy for neck and upper extremity pain.Methods: Systematic literature search was performed for studies reporting ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…A large randomized controlled trial (RCT) demonstrated its safety and superior effectiveness for the treatment of back and leg pain over T-SCS 16,17 along with improved quality of life and opioid reduction. 15,[18][19][20][21][22][23] The results were confirmed by other retrospective and prospective studies in patients with back and leg pain. 22,[24][25][26][27][28][29][30] Prospective and retrospective studies have also demonstrated promising outcomes for the treatment of migraine headaches, 31 complex regional pain syndrome (CRPS), 32 chronic widespread pain, 33 pelvic pain, 34 upper and lower limb neuropathic pain, 35,36 and neck pain.…”
supporting
confidence: 81%
“…A large randomized controlled trial (RCT) demonstrated its safety and superior effectiveness for the treatment of back and leg pain over T-SCS 16,17 along with improved quality of life and opioid reduction. 15,[18][19][20][21][22][23] The results were confirmed by other retrospective and prospective studies in patients with back and leg pain. 22,[24][25][26][27][28][29][30] Prospective and retrospective studies have also demonstrated promising outcomes for the treatment of migraine headaches, 31 complex regional pain syndrome (CRPS), 32 chronic widespread pain, 33 pelvic pain, 34 upper and lower limb neuropathic pain, 35,36 and neck pain.…”
supporting
confidence: 81%
“…Most reviews considered all types of implants, with two reviews considering only percutaneous implants27 30 and five not specifying the type of implant. Nearly two-thirds considered mixed or all types of stimulation, with eight considering only CS, two on HFS14 71 and one on burst stimulation (BS) 18. The most common comparator was conventional medical management (CMM), although some compared different SCS types, with one comparing BS, CS, and HFS,35 and two others comparing BS and CS 18 32.…”
Section: Resultsmentioning
confidence: 99%
“…15 The results reported are equal to, if not better than, pain relief with 10-kHz SCS recorded in other pain types like back pain and upper limb and neck pain. 28,[37][38][39][40] At 3 months after implantation, 79% of patients in the intention-to-treat population achieved ≥50% pain relief plus no worsening of baseline neurological deficits, compared with only 5% of CMM patients (P < .001; study primary end point). 15 In terms of pain relief alone at 3 months, 78% of patients reported pain scores of 3 cm or less on the VAS (P < .001 vs 5% with CMM).…”
Section: Neuromodulation For Patients With Refractory Painmentioning
confidence: 99%